2017
DOI: 10.1175/jcli-d-16-0693.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Warming in the Kara Sea and Barents Sea during the Winter Period 2000–16

Abstract: The regional climate model COSMO in Climate Limited-Area Mode (COSMO-CLM or CCLM) is used with a high resolution of 15 km for the entire Arctic for all winters 2002/03–2014/15. The simulations show a high spatial and temporal variability of the recent 2-m air temperature increase in the Arctic. The maximum warming occurs north of Novaya Zemlya in the Kara Sea and Barents Sea between March 2003 and 2012 and is responsible for up to a 20°C increase. Land-based observations confirm the increase but do not cover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 50 publications
4
39
0
1
Order By: Relevance
“…It is important to continue to capture the accelerated climate changes According to this analysis, the strongest statistically significant trends have occurred in the Kara and Barents Seas around the island of Novaya Zemlya (68°-80°N, 60°-90°E). This is consistent with the analysis by Kohnemann et al (2017) showing that a reduction of sea ice in this region in late autumn and winter is a driver of enhanced ocean-atmosphere sensible heat flux. The Novaya Zemlya trends for this time period are approximately 40%, nearly 4 times the basinwide sea ice extent decline across the Arctic.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to continue to capture the accelerated climate changes According to this analysis, the strongest statistically significant trends have occurred in the Kara and Barents Seas around the island of Novaya Zemlya (68°-80°N, 60°-90°E). This is consistent with the analysis by Kohnemann et al (2017) showing that a reduction of sea ice in this region in late autumn and winter is a driver of enhanced ocean-atmosphere sensible heat flux. The Novaya Zemlya trends for this time period are approximately 40%, nearly 4 times the basinwide sea ice extent decline across the Arctic.…”
Section: Discussionsupporting
confidence: 92%
“…4). The great winter warming in this area was also more recently noted among others by Alexeev et al (2017), Jung et al (2017) and Kohnemann et al (2017). Graham et al (2017) found that, in the period of interest, a significantly greater frequency and duration of Arctic winter warming events (see their Fig.…”
Section: Instrumental Observationssupporting
confidence: 78%
“…The areas in the western Barents Sea and around Svalbard, where we find significant positive trends in cyclone densities in winter (Regions A and B), have also experienced other rapid recent changes. These include the globally highest rates of wintertime 2 m air temperature increase (Førland et al, 2011;Kohnemann et al, 2017) and the most rapid winter sea ice decline (Parkinson and Cavalieri, 2008;Screen and Simmonds, 2010). In addition, Årthun et al (2012) show that the oceanic heat inflow into the Barents Sea has increased and that this inflow controls the location of the sea ice margin in the western Barents Sea.…”
Section: Discussionmentioning
confidence: 99%
“…The Arctic climate system is transferring into a warmer and wetter state as a result of the unequivocally warming climate (Intergovernmental Panel on Climate Change, 2013; Vihma et al, 2016). The Arctic is warming fastest in the autumn and winter seasons (Cohen et al, 2014), and the highest warming rates are found around Svalbard and over the Barents Sea (Isaksen et al, 2016;Kohnemann et al, 2017). These areas have, in addition to rapidly rising air temperatures, experienced the highest rates of wintertime sea ice loss (Smedsrud et al, 2010;Onarheim et al, 2015;Onarheim and Årthun, 2017;Lind et al, 2018) in the last few decades.…”
Section: Introductionmentioning
confidence: 99%